Morphology Analysis Derivation and Inflectional in Katy Perry Album "Prism" - Hasbi, Muhammad Dipo; Huda, Ahmad Nur; Siregar, Otto (Linguistics and ELT Journal, 2024)
This research looks at the morphological elements of Katy Perry's Prism album lyrics, focusing on derivational and inflectional morphemes. Morphology is a branch of linguistics that focuses on the role of morphemes in language and examines the structure, meaning, and creation of words. With 33 occurrences, the most common derivational suffix, according to the data, is -ing. -ly (8 instances), un- (4), -y (3), and -er (2) come after it. Less frequent suffixes, such -ary, -ity, and others, only occur once each. The most frequent prefix is un-, which appears six times, while in-(2) and uni-(1) are less frequent. The most frequent inflectional morphemes are plural forms and past participles, which occur 18 times each, showing how important they are in showing multiplicity and completed actions. Comparative degrees appear 6 times, and the past tense is used 7 times, further indicating the richness of grammatical forms that the album expresses. The results reveal the linguistic diversity of PRISM's song lyrics, which deliver the messages of relationships, self-determination, and living in the present through a harmony of derivational and inflectional processes. This research contributes to our understanding of how morphological elements enhance the literary works and promote vocabulary acquisition through song lyrics.